Ag‐nanoparticle embedded p(AA) hydrogel as an efficient green heterogeneous Nano‐catalyst for oxidation and reduction of organic compounds. (23rd June 2017) - Ghorbanloo, Massomeh; Heydari, Ali; Yahiro, Hidenori
Abstract : P(AA)‐Ag heterogeneous catalyst system comprised of Ag nanoparticles embedded within hydrogel matrices has been described for the selective aerobic oxidation of alcohols and reduction of nitro phenols in water. P(AA)‐Ag nanocomposite was characterized by Fourier transform infrared (FT‐IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), thermal gravimetric analysis (TGA), X‐Ray photoelectron spectroscopy (XPS) and inductively coupled plasma atomic emission spectrometer (ICP). Catalytic activity of p(AA)‐Ag catalyst was investigated in the aerobic oxidation of primary alcohols and reduction of nitro compounds by emphasizing the effect of different parameters such as temperature, catalyst amount, substituent effect, etc . The catalyst was easily recovered from the reaction medium and it could be re‐used for other three runs without significant loss of activity. Abstract : p(AA)‐Ag heterogeneous catalyst system has been described for the selective aerobic oxidation of alcohols in water. In the presence of the Ag catalyst, within 24 h and with 0.036 mmol Ag, 79% isolated yield of the benzoic acid and 1.96% yield of the benzaldehyde were obtained.